Japan City Pop Music Trend Contribution to Cool Japan Soft Power Diplomacy Program In The 2020s - Fadya Almira Wardhana; Daniel Hermawan (Universitas Diponegoro, 2024)
The soft power diplomacy has been used by Japan since the end of WWII and post bubble economy, and was officialized as ‘Cool Japan’ program which includes all aspects of Japanese culture and cultural products. On the other hand, ‘city pop’, a genre popular in Japan around the 80’s, surfaced again in the 2020’s as a result of YouTube’s algorithm, and has been a trend on the internet with many global fans. The purpose of this research was to find out whether Japan city pop music trend contributes to Cool Japan program, with mixed method approach and data collecting method of online survey on Japan city pop fans in Indonesia. It is then concluded that Japan city pop has been contributing to Cool Japan by meeting it’s main goal and strategies of creating Japan’s image as a cool nation on its own. <a href=